Shakespeare's secret - Broach, Elise (Square Fish, 2007)
Named after a character in a Shakespeare play, misfit sixth-grader Hero becomes interested in exploring this unusual connection because of a valuable diamond supposedly hidden in her new house, an intriguing neighbor, and the unexpected attention of the most popular boy in school.